Adult plant leaf rust (Puccinia recondita tririci) resistance of known Lr genes against three virulence variants of race 77 from Indian sub-continent - SAINI, R G; KAUR, LIVINDER; KAUR, MANDEEP (The Indian Journal of Agricultural Sciences, 2013)
The seedling and adult plant response of known leaf rust resistance genes Lr1 through Lr45 was studied againstvirulence variants 77-1, 77-2 and 77-5 of race 77. The lines having alien genes Lr9, Lr18, Lr19, Lr24, Lr25, Lr28,Lr29, Lr32, Lr41, Lr42 and Lr45 showed hypersensitive seedling resistance against these variants. Therefore, the adultplants from lines with these genes remained highly resistant in field tests also. The gene Lr30 was the only source of suchresistance from Triticum aestivum L. emend. Fiori & Paol. The field grown adult plants of lines with the genes Lr2a,Lr3ka, Lr14b, Lr21. Lr22a, Lr33, Lr34,b35, Lr37, Lr38, Lr43 and Lr44. showed moderate to high degree of partialresistance. The adult plants from Hnes with the genes Lr1, Lr2h, Lr2c, Lr2d, Lr3(Do), Lr3(Bg), Lr1O, Lr11, Lr13,Lr14a, Lr15, Lr16, Lr17, Lr20, Lr22b, Lr23, Lr27, Lr31, and Lr36. were susceptible to one or more of the variants77-1, 77-2 and 77-5 in field tests.